Drought impacts to water footprints and virtual water transfers of the Central Valley of California. Issue 7 (18th July 2017) - Marston, Landon; Konar, Megan
Abstract: The Central Valley of California is one of the most productive agricultural locations in the world, which is made possible by a complex and vast irrigation system. Beginning in 2012, California endured one of the worst droughts in its history. Local impacts of the drought have been evaluated, but it is not yet well understood how the drought reverberated through the global food system. Here we quantify drought impacts to the water footprint ( WF ) of agricultural production and virtual water transfers ( VWT ) from the Central Valley of California. To do this, we utilize high‐resolution spatial and temporal data sets and a crop model from predrought conditions (2011) through 3 years of exceptional drought (2012–2014). Despite a 12% reduction in harvested area, the WF of agricultural production in the Central Valley increased by 3%. This was due to greater crop water requirements from higher temperatures and a shift to more water‐intensive orchard and vine crops. The groundwater WF increased from 7.00 km 3 in 2011 to 13.63 km 3 in 2014, predominantly in the Tulare Basin. Transfers of food commodities declined by 1% during the drought, yet total VWT increased by 3% (0.51 km 3 ). From 2011 to 2014, groundwater VWT increased by 3.42 km 3, offsetting the 0.94 km 3 reduction in green VWT and the 1.96 km 3 decrease in surface VWT . During the drought, local and global consumers nearly doubled their reliance on the Central Valley Aquifer. These results indicate that drought may strengthen the telecoupling between groundwater withdrawals and distant consumers of agricultural commodities. Key Points: The groundwater footprint of agricultural production increased with the California drought, predominantly in the Tulare Basin Food transfers declined over the course of the drought, but total virtual water transfers increased, driven by embodied groundwater Local and global consumers doubled their reliance on the already overexploited Central Valley Aquifer during the drought